PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP KREATIVITAS SISWA SMA KELAS XI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA - Intan Ratna Juwita; Andrie Djatmiko, Andreas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of Artificial Intelligence (AI) usage and critical thinking ability on the creativity of eleventh-grade students in Pancasila Education learning at SMA Negeri 1 Kauman. This study employed a quantitative approach with a survey method. The study population consisted of all eleventh-grade students at SMA Negeri 1 Kauman, with a sample of 216 students selected using proportional random sampling technique. The research instrument used was a questionnaire with a 1–5 Likert scale that had been tested for validity and reliability. The data analysis technique used was multiple linear regression analysis. The results showed that: (1) there is a positive and significant effect of AI usage on student creativity, with t-count 2.540 > t-table 1.971 and significance 0.015 < 0.05; (2) there is a positive and significant effect of critical thinking ability on student creativity, with t-count 15.128 > t-table 1.971 and significance 0.000 < 0.05; (3) there is a positive and significant simultaneous effect of AI usage and critical thinking ability on student creativity, with F-count 113.919 > F-table 3.04 and significance 0.000 < 0.05. The coefficient of determination (R²) of 0.517 indicates that both independent variables jointly contribute 51.7% to student creativity. The regression equation obtained is Y = 9.219 + 0.006X₁ + 0.620X₂. Critical thinking ability proved to be a more dominant factor than AI usage in influencing student creativity. All three variables were at a moderate category, meaning they have formed and are running, but are not yet consistent and not yet optimal.